(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Urine cytology is a simple, rapid, non-invasive, and cost-effective diagnostic tool widely used in the evaluation of urinary tract disorders. It plays an important role in patients presenting with hematuria, aiding in the detection of infections, urolithiasis, and urothelial malignancies. The presence of atypical urothelial cells in urine poses a diagnostic challenge, as it may be associated with both benign and malignant conditions. Aim: To evaluate the cytological features of atypical cells in urine samples from patients with hematuria and to determine their clinical significance. Materials and Methods: This descriptive study was conducted in the Department of Pathology at Sree Mookambika Institute of Medical Sciences from June 2025 to February 2026. A total of 4015 freshly voided urine samples were analyzed. Samples were processed by centrifugation at 1500 rpm for 30 minutes, and smears were prepared from the sediment and stained using routine cytological stains. Detailed microscopic examination was performed to identify atypical and malignant cells. In selected cases, three consecutive urine samples were analyzed to improve diagnostic yield. Statistical analysis was carried out using descriptive and inferential methods, with a p-value <0.05 considered significant. Results: A spectrum of cytological findings was observed, ranging from benign to atypical and malignant lesions. Atypical urothelial cells were identified in a subset of hematuria cases and showed variable association with underlying pathological conditions. Malignant cells were more frequently associated with high-grade urothelial carcinoma. The use of multiple samples improved detection rates. Conclusion: Urine cytology is an effective adjunctive tool in the evaluation of hematuria, particularly for detecting high-grade malignancies and monitoring recurrence. The presence of atypical cells warrants careful interpretation and further investigation. When combined with clinical and cystoscopic findings, cytology significantly enhances diagnostic accuracy and patient management.